Brief Report: Low Incidence of Hepatitis C Among a Cohort of HIV-Negative Gay and Bisexual Men Using HIV Pre-exposure Prophylaxis (PrEP) in Melbourne, Australia, and the Contribution of Sexual Transmission. (1st August 2021) - Cornelisse, Vincent J.; Traeger, Michael W.; Wright, Edwina J.; Murphy, Dean; Stoové, Mark; Hellard, Margaret; Sacks-Davis, Rachel; Asselin, Jason; Fairley, Christopher K.; Doyle, Joseph; Sasadeusz, Joseph
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: PrEPX was an Australian HIV pre-exposure prophylaxis (PrEP) study conducted between 2016 and 2018. This analysis aimed to estimate hepatitis C (HCV) incidence and explore likely modes of transmission. Setting: Cohort study of PrEP users in Victoria, Australia. Methods: HCV tests were conducted at enrollment and every 12 months thereafter. HCV incident cases were identified from laboratory data. Likely modes of transmission were inferred from computer-assisted self-interviews, medical records, and interviews. Results: Among 3202 PrEPX participants tested for HCV at baseline, HCV RNA-positive prevalence was 0.22% (95% confidence interval: 0.09 to 0.45). Among participants testing HCV antibody-negative or RNA-negative at baseline, 2058 had at least one follow-up HCV test. Eight incident HCV cases were identified during 2111 person-years of follow-up (incidence 0.38/100 person-years); all were primary infections in men who had sex with men. Clinical, laboratory, and computer-assisted self-interviews data were available for all, and 6 cases were interviewed. Three cases were attributable to injecting drug use (IDU). A fourth case reported IDU, but his HCV was attributable to sexual transmission. Four other cases reported no IDU and probably acquired HCV sexually. Most cases reported anal trauma in the context of condomless receptive anal intercourse during group sex at sex-on-premises venues. Conclusions: In PrEPX, HCV incidence was low compared to international PrEP studies, and most cases were transmitted sexually. Our findings highlight the need for HCV prevention messaging by clinicians, in sex-on-premises venues, and on digital platforms used to arrange group sex; and the need for HCV screening among some PrEP-using men who have sex with men.